Religious Education's Relevance in Nigeria's Tertiary Institutions - Peter O. O. Ottuh; Jonathan O. Ihwighwu (Khazanah Pendidikan Islam, 2023)
This study aimed to determine how important religious education is in Nigerian schools, especially in tertiary institutions in the Delta State of Nigeria. To reach this goal, eleven colleges and universities in Delta State were chosen for the research. Research questions and hypotheses were formulated to guide the study. The data for the study was collected from primary sources using a structured questionnaire. Twenty-two questionnaires were administered to the selected institutions' twenty-two heads (and deputies). Means and Standard Deviations (M & SD) were used to answering the research questions, and the hypotheses were tested using the t-test statistical method. The findings of this study led to the conclusion that there are significant differences in tertiary institutions' heads' perceptions of the relevance of religious education in tertiary institutions in Delta State for the effective curbing of moral decadence in the state and the Nigerian society as a whole.